Melatonin reduces cell motility and antioxidant defenses in ovarian cancer cell lines - Silveira, Henrique Spaulonci [UNESP]; Cesário, Roberta Carvalho [UNESP]; Simão, Vinicius Augusto [UNESP]; Guimarães, Fernando; Seiva, Fábio Rodrigues Ferreira [UNESP]; Zuccari, Debora Aparecida P. C.; Fernandes, Glaura Scantamburlo Alves; de Souza, Milena Cremer; Reiter, Russel J.; Chuffa, Luiz Gustavo de Almeida [UNESP] (Springer Nature, 2025)
Ovarian cancer (OC), a highly recurrent and fatal tumor, poses diagnostic challenges due to generic symptoms and chemoresistance. Melatonin (Mel) is an indoleamine acting against tumor progression and exhibiting pro-oxidative actions in tumor cells. This study explores the impact of Mel on antioxidant defenses of OC cells (SKOV-3 and CAISMOV-24 lines), focusing on its receptor-dependent and -independent effects. Cell viability was assessed using the MTT method and the antioxidant system was analyzed by preparing supernatants for assessing glutathione (GS), reduced glutathione (GSH), oxidized glutathione (GSSG), catalase (CAT), glutathione S-transferase (GST), and superoxide dismutase (SOD). Mel stimulated its own intracellular levels, reducing cell viability in both cell lines. Notably, Mel independently of its membrane receptors, inhibited migration and invasion, thus showing its anti-tumoral potential. By investigating melatonin’s actions, we observed an impact on the antioxidant system primarily through the reduced activity of CAT and the GS axis. The modulation of these antioxidants by Mel demonstrates its multifaceted role in OC, emphasizing its therapeutic potential. We also demonstrated, for the first time, the theoretical ability of Mel to bind to CAT, which may be responsible for the reduction in enzyme activity. This study contributes with novel insights into Mel's receptor-independent actions, providing a foundation for further research in OC therapy.